2018
DOI: 10.1186/s40580-018-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional inorganic nanotubes f-INTs-WS2 on hemolysis, platelet function and coagulation

Abstract: Inorganic transition metal dichalcogenide nanostructures are interesting for several biomedical applications such as coating for medical devices (e.g. endodontic files, catheter stents) and reinforcement of scaffolds for tissue engineering. However, their impact on human blood is unknown. A unique nanomaterial surface-engineering chemical methodology was used to fabricate functional polyacidic polyCOOH inorganic nanotubes of tungsten disulfide towards covalent binding of any desired molecule/organic species vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…[159] In vivo long-term toxicology of TMDC (WS 2 , TiS 2 , MoS 2 ) has also been testified by Hao et al [160] According to their research, there was no obvious long-term toxicity of WS 2 nanosheets at the tested dose, despite it being difficult to oxidize WS 2 , and thus it showed much longer in vivo retention. However, severe side effects, such as obvious hepatic function impairment [161] and hemolysis/platelet/coagulation dysfunction [162] have been reported. In addition, some studies have attempted to elucidate the mechanism of TNMs in cells.…”
Section: Toxicity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…[159] In vivo long-term toxicology of TMDC (WS 2 , TiS 2 , MoS 2 ) has also been testified by Hao et al [160] According to their research, there was no obvious long-term toxicity of WS 2 nanosheets at the tested dose, despite it being difficult to oxidize WS 2 , and thus it showed much longer in vivo retention. However, severe side effects, such as obvious hepatic function impairment [161] and hemolysis/platelet/coagulation dysfunction [162] have been reported. In addition, some studies have attempted to elucidate the mechanism of TNMs in cells.…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Based on the above research, although TNMs show excellent biocompatibility and safety in cell experiments, they still require extreme caution for application in human bodies owing to potential hazards such as thrombosis and mutagenicity. [158,162] In addition, a relevant toxicity evaluation standard or system needs to be formulated as soon as possible to promote its possible clinical application.…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Raichman et al used a highly electrophilic acidic Vilsmeier-Haack reagent to produce polycarboxylated functional WS 2 nanotubes that can be dispersed in polar liquids 16 . In 2018, they also found that the functionalised WS 2 is biocompatible and may come into contact with blood, indicating a high degree of biocompatibility 17 . However, there have only been a limited number of studies focussing on the preparation of WS 2 thin sheets via liquidphase exfoliation and the application of these sheets [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hemolysis assay was performed according to the ASTM E2524-08 standard protocol to evaluate the hemocompatibility of the NPs. 26 For this purpose, whole human blood was acquired from ZenBio and used according to the institutionally (UCLA) approved safety protocols. Blood was stored in heparinized tubes, refrigerated, and used in the assay not later than 48 h. Concentration of the hemoglobin in the blood was estimated by Drabkin's reagent, using a standard curve generated on different concentrations of pure human hemoglobin (1000–62 μg ml −1 ).…”
Section: Methodsmentioning
confidence: 99%